EFFICIENCY OF VALVE BRONCHIAL BLOCK AS A PART OF THE COMPREHENSIVE TREATMENT OF DESTRUCTIVE PULMONARY TUBERCULOSIS WITH CONCURRENT HIV INFECTION - Ya. K. Petrova; D. V. Krasnov; S. V. Sklyuev; T. V. Zyryanova (Туберкулез и болезни лёгких)
Goal of the study: to enhance the efficiency of the comprehensive treatment of destructive pulmonary tuberculosis in HIV patients using bronchial valve block.Materials and methods. A study was conducted enrolling two groups of tuberculosis patients with destructive drug resistant pulmonary forms and concurrent HIV infection having comparable clinical and laboratory characteristics. Treatment of the patients in the main group (n = 68) included valve bronchial block. Patients from the comparison group (n = 57) received the same treatment but without valve bronchial block.Results of the study. Adding valve bronchial block to the treatment of tuberculosis is a positive factor confidently promoting sputum conversion (OR = 4.13; 95% CI 3.50-4.75) and healing of cavities (OR = 3.89; 95% CI 3.30-4.48). When using valve bronchial block the healing of cavities made 55.9%, while in the comparison group it made only 24.6%; (p = 0.0004, χ2 ). Sputum conversion was achieved in 75.0%, and in the comparison group, this rate was 42.1% (p = 0.0002, χ2 ). The above rates varied respectively the degree of immunosuppression in the patients.